Novel electrode material using electroless nickel plating for triboelectric nanogenerator: Study of the relationship between electrostatic-charge density and strain in dielectric material. (February 2022) - Huang, Junjun; Wu, Wangping; Zhang, Ruxia; Lu, Guoqing; Chen, Bing; Chen, Zhenming; Gui, Chengmei
Abstract: Cu/Ag foils or conducting pastes were proposed and developed to fabricate the electrodes for triboelectric nanogenerators (TENGs) on support surface. But the technology is limited by the substrate surface morphology, especially complex shape and high roughness substrate. In this study, electroless nickel plating on polyethylene terephthalate surface for TENGs electrode was established, the output performances under different external forces were studied comprehensively to obtain a full understanding of the relationship between the density of electrostatic charge (δ) and strain of polydimethylsiloxane (PDMS) dielectric material. Results showed that PET modified with primer (SiO2 particles-resin mixed liquors) could absorb Pd 2+ through coordination effect, which acted as catalyst for the deposition of Ni coating on its surface. The deposition of bead-like structure Ni coating on PET surface with a higher average roughness value (Sr) possessed excellent crystallization and electrical property. The TENGs device with Ni coating electrode was measured and compared. The results showed that the relationship between its output electrical signal and SiO2 content in the primer also presented a similar trend for the Sr. The TENGs device had stable and excellent performances and yielded a maximum open-circuit voltage of 39 V. More importantly, a new calculation method for the PDMS strain of formation δ was proposed by equation of state. It was also revealed that the δ and PDMS strain represented a linear regression relation, and the formation of vertical intercept is due to TENGs device internal resistance. This work proposes a visible solution for the flexible, low-cost and lightweight TENGs, and offer the quantitative information about the influences of dielectric material strain on the output performance which could not be reported so far. Graphical abstract: ga1 Highlights: Electroless nickel plating on polyethylene terephthalate surface for TENGs electrode was established. The TENGs electrode with higher average roughness value would facilitate the improvement of device performance. The output performance under different external force were studied comprehensively to obtain a full understanding of the relationship between electrostatic-charge density and PDMS strain.